Pelatihan Renang Pertolongan Guru–Guru Penjas Di Kabupaten Sumedang Jawa Barat - Kholik, Abdul; Ali, Masnur; Zulham, Zulham (Prosiding Seminar Nasional Pengabdian Masyarakat, 2024)
Rescue swimming is one form of specific swimming techniques used to help people who are about to drown or who are drowning. Rescue swimming is very important to be mastered by teachers, especially PE teachers. Because in addition to aquatic / swimming lessons in schools, sometimes school PE teachers are actively involved in outdoor activities such as in swimming pools, rivers lakes and beaches. It can be imagined that if the PE teachers do not master good and correct rescue swimming techniques, there will be many victims / students who cannot be helped if there are cases of drowning when students take aquatic / swimming lessons or there are outdoor activities in rivers, lakes and beaches. Moreover, the Conggeang area now has many swimming pools, rivers, and lakes/ponds/situ. Therefore, with this rescue swimming training, it is hoped that the PE teachers in the Conggeang area will be proficient in mastering rescue swimming techniques, so that when there is a case of drowning in the swimming pool that befalls their students or public people both in lakes and rivers they can help victims of drowning easily and safely.